Gerard Manley Hopkins’s Incarnational Ecology - Cochran, James M. (Religion and the arts, 2017)
This essay examines Hopkins’s “Binsey Poplars” from an incarnational theological lens. Such a reading negotiates seemingly incongruent arguments put forth by Post, who argues that Hopkins’s ecological world is “other,” and Day, who argues that Hopkins makes the ecological world comprehensible. Incarnational theology allows for a middle ground by preserving beings’ uniqueness yet unifying them in a collective body. Additionally, reading the poem from an incarnational theological lens continues recent critical work that sees religious dimensions in the poem. Finally, this essay suggests that Hopkins’s incarnational theology anticipates and speaks to contemporary ecological and ecocritical issues. As such, this essay reads contemporary and emerging ecocritical voices alongside Hopkins’s poem to demonstrate the harmony between the theological and theoretical voices.